Right Sided Trouble: Persistent Shunting after Iatrogenic Atrial Septal Defect Closure with an Amplatzer PFO Occluder Treated Successfully With a Cardioform Septal Occluder - Stauber, Bradley; Nibley, Carleton; Lim, Wayland; Rogers, Jason H. (Cardiology and Cardiovascular Medicine, 2019)
We describe a patient with severe, symptomatic platypnea-orthodeoxia after an atrial fibrillation ablation leading to an iatrogenic atrial septal defect. The shunt was initially closed with Amplatzer PFO occluder, however with continued symptoms and brisk flow through the device, an alternative solution had to be devised. After removal of the device and placement of a Gore Cardioform septal occluder sealed the defect, alleviating symptoms almost instantaneously. To our knowledge, this is the first such case reported.